The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1128/iai.02060-14
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensis LVS Induction of Prostaglandin Biosynthesis by Infected Macrophages Requires Specific Host Phospholipases and Lipid Phosphatases

Abstract: Francisella tularensis induces the synthesis of prostaglandin E 2 (PGE 2 ) by infected macrophages to alter host immune responses, thus providing a survival advantage to the bacterium. We previously demonstrated that PGE 2 synthesis by F. tularensis-infected macrophages requires cytosolic phospholipase A2 (cPLA 2 ), cyclooxygenase 2 (COX-2), and microsomal prostaglandin E synthase 1 (mPGES1). During inducible PGE 2 synthesis, cPLA 2 hydrolyzes arachidonic acid (AA) from cellular phospholipids to be converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…To investigate the contribution of lipin-1 to foam cell formation, we used the RAW264.7 macrophage cell line, in which we generated stable lipin-1 knockdown using a lentivirally delivered shRNA (80% knockdown). We have previously demonstrated both the successful and specific knockdown of lipin-1 in RAW264.7 macrophages 15 . Wild-type (WT), non-target (NT) or lipin-1 depleted RAW264.7 macrophages were mock treated or treated with oxLDL (10 μg/mL) or acLDL (50 μg/mL) for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the contribution of lipin-1 to foam cell formation, we used the RAW264.7 macrophage cell line, in which we generated stable lipin-1 knockdown using a lentivirally delivered shRNA (80% knockdown). We have previously demonstrated both the successful and specific knockdown of lipin-1 in RAW264.7 macrophages 15 . Wild-type (WT), non-target (NT) or lipin-1 depleted RAW264.7 macrophages were mock treated or treated with oxLDL (10 μg/mL) or acLDL (50 μg/mL) for 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…Macrophages require lipin-1 for PGE 2 and pro-inflammatory cytokine production in response to LPS and the intracellular bacteria Francisella tularensis 1516 . We demonstrate here that short-term oxLDL treatment (24 hours) fails to elicit pro-inflammatory cytokine responses, in agreement with work by Spann et.al, who demonstrated that cholesterol uptake by macrophages results in an anti-inflammatory macrophage phenotype 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased survival outcome resulting from the reduction of PGE2 production during bacterial infections through COX-2 inhibition and reduction in NF-ĸB activation has profound implications. PGE2 is produced during a number of lethal bacterial infections (i.e Francisella tularesis [23]) and opportunistic bacterial infections ( Pseudomonas aeruginosa and Staphylococcus aereus ) for which antibacterial treatment is complex due to antibacterial resistance [24] [25]. Proving the efficacy of immunotherapy using commercially available, orally administered TA in combination with sub-therapeutic antibiotic treatment during melioidosis in BALB/c mice warrants further investigation in other animal models of melioidosis.…”
Section: Discussionmentioning
confidence: 99%
“…44 Once differentiated, BMDM were washed with PBS, seeded for the appropriate downstream assay, allowed to adhere for 2 hours in complete DMEM, and subsequently incubated with conditioned media (CM) from control and colitic acute 2% DSS-induced C57BL/6J mice, as previously described. 17 In the IF groups, CM was supplemented with cytochalasin D (10 μm; Sigma).…”
Section: Methodsmentioning
confidence: 99%